Quem conta o conto controla o ponto: narrador e pontos de vista em Levantado do chão, Memorial do convento e O ano da morte de Ricardo Reis, de José Saramago - Adorno, Karen Lorrany Neves (2024)
This thesis studies four elementary narrative modes actively attached to the notion of points of view in Raised from the ground (1980), Baltasar and Blimunda (1982) and The year of death of Ricardo Reis (1984), by Portuguese author José Saramago. Those modes are: the tangenciality from the official historiography to the unofficial and/or the fictional, the discursive sinuosity, the empathy and the sympathy, the antipathy and the irony as methods that unchain argumentative-narrative guidelines of the speech. The main focus of this research falls upon the narrators' identity and the implied points of view of the narratives, whether they are related to the narrator beings or to the characters. The established analysis seeks to demonstrate that the narrators of the three romances have modal competencies related to duty, power, knowledge, will and action. They enrich the narrative modus operandi taking, besides the strictly narrative function, ideological and testimonial roles. The narrator beings manifest in the first enunciative function, moving from the timelessness level of the narrative in order to submit themselves to the temporality level of the narrative. By these narrative "deviations", the narrators cannot be denominated just as disembodied voices that do not participate of the histories whose function exclusively achieve the control of the text information. The identity complexity and the narrative modus operandi of these narrative beings opens space to the creation of a new concept of narrator, named anthropologized narrator. They are creators of points of view with the ability of putting themselves on the place of the other, of feeling empathy, sympathy and antipathy to weave and convince their readers. Reinforcing several studies about the axiological positions clearly taken by saramagian narrators, this research is firstly turned to the narration and focalization mechanisms in order to demonstrate the methods through which such ideological and axiological narrators’ intentions acquire materiality and functionality in the discursive dynamics. The study is segmented in five parts, investigating, respectively, four narrative modes employed by the narrators: the tangenciality from the official historiography to the unofficial and/or fictional, analyzed in chapter 3; the discursive sinuosity, discussed on the subchapter 3.1; the empathy and the sympathy as argumentative-narrative method, studied on chapter 4; the antipathy and the irony as an argumentative harangue disputed by the narrators, focus of chapter 5. The theoretical support of the six chapters includes Genette (1995), Landa (1998), Hutcheon (2000), Rabatel (2014 and 2016) and Bal (2021).